Level of Education and Parity of Pregnant Women with Anemia Incidence in Coastal Health Center Tarakan City, North Kalimantan - Andi Yuniarsy Hartika; Gusni Fitri; Armina Armina (Universitas Teuku Umar, 2023)
The prevalence of anemia for pregnant women in the coastal area of Tarakan City is the highest in 2021, namely 53.5%, which is far above the national target of 45%. This study aimed to determine the relationship between education level and parity of pregnant women with the incidence of anemia in the coastal area of Tarakan City in 2021. The type of research used was analytic observational with a cross-sectional research design. The population is all pregnant women in the third trimester at the Pantai Amal Community Health Center in 2021. The sample size for this study was 97 pregnant women with a random sampling technique. Data was collected using medical record data at the Amal Beach Health Center in 2021 and then analyzed using Chi-Square with p = 0.05. The analysis of the relationship between education level and the incidence of anemia in pregnant women at the community health centre in the coastal area of Tarakan City showed a significant relationship (p=0.005). The relationship between parity and the incidence of anemia in pregnant women also showed a significant relationship where as many as 39 mothers (40.2%) with parity were at risk of developing anemia. There is a significant relationship between education level and parity with the incidence of anemia in pregnant women at Amal Beach Health Center. Therefore, developing a program to prevent anemia in pregnant women at the Amal Beach Health Center is essential by considering the significant risk factors associated with anemia.